Planning tool for fiber optic communication systems: access and transport network - Horta, Gonçalo Miguel da Silva (2016)
This thesis aims to develop a software, Fiber Optic Planning Tool (FOPT) that is an efficient and modern software pack developed for planning of telecommunication systems for point-to-point fiber optic links. The system planning is divided into two parts: the transport network and the access network, and the route is chosen by using Google Maps (GM) that is integrated in the FOPT. This tool contains a very interesting didactic component for graduation and post-graduation telecommunications students and, on the other hand for telecommunications engineers that need to make a technical-economic project guided by fiber optic as a communication system. The tool allows you to choose components and equipment that exist in the market (it considers several suppliers) according with the network type. This allows to obtain the partial and total project costs. The user can also add new components to the database. The tool is built by several blocks that the user must fill sequentially to obtain the best solution for the planning. The results given by the tool are compared with the requirements of ITU-T recommendations, showing whether the obtained values reach the established standards. This tool is efficient, modern, very user friendly and it might simplify the techno-economic project of fiber-optic networks. This tool was developed in Java, a rich and versatile programming language capable of interacting with other languages and softwares. It was necessary to use several integrated libraries of Java for graphing, for managing the data in the database and for the execution of mathematical operations. For the insertion and management of data in the database was used Structured Query Language (SQL) and Hypertext Preprocessor (PHP).